Clinical and MRI Differences Between Patients With Subacute Combined Degeneration of the Spinal Cord Related vs. Unrelated to Recreational Nitrous Oxide Use: A Retrospective Study - Gao, Han; Li, Weishuai; Ren, Jing; Dong, Xiaoyu; Ma, Ying; Zheng, Dongming (Frontiers in Neurology, 2021)
Objective: To explore the clinical and imaging characteristics of subacute combined degeneration of the spinal cord (SCD) related to recreational nitrous oxide (N2O) use. Methods: Clinical and imaging data were retrospectively collected from patients with SCD related to recreational N2O use who were diagnosed and treated at Shengjing Hospital from January 2016 to June 2020. The clinical and imaging features of patients with recreational N2O-related SCD were compared with those of patients with N2O-unrelated SCD. Results: The study enrolled 50 patients (male/female: 22/28, age: 21.4 ± 4.7 years) with N2O-related SCD and 48 patients (male/female: 27/21, age: 62.0 ± 11.4 years) with SCD unrelated to N2O use. The incidence of limb weakness, unsteady gait, disorders of urination and defecation, anorexia, reduced deep sensation, ataxia, and positive Babinski sign were lower in the N2O-related SCD group than those in the N2O-unrelated SCD group (P<0.05). The functional disability rating score of patients in the N2O-related SCD group was also significantly lower than the score in the N2O-unrelated SCD group. The serum vitamin B12 level was significantly lower in the N2O-unrelated SCD group than the level in the N2O-related SCD group, while both groups had similarly increased levels of homocysteine. Compared with the N2O-unrelated SCD patients, more patients with N2O-related SCD had abnormal spinal magnetic resonance imaging (MRI) scans (80.0 % vs 64.2 %). Conclusion: Compared with the N2O-unrelated SCD patients, the N2O-related SCD patients had less severe clinical presentations, less obvious decrease in serum VB12 levels, and more obvious MRI changes.